Impact of social network on cardiovascular mortality in middle aged Danish men. Issue 3 (June 1993) - Olsen, O
Abstract : STUDY OBJECTIVE--To estimate quantitatively (the aetiological fraction) the impact of poor social network on premature death from cardiovascular disease in middle aged, white men. DESIGN--The causality of the relationship has already been discussed in a large review, and it is assumed to be well documented. The numerical estimation of the impact was based on a review of all published cohort studies on the relationship between social network and mortality in white, middle aged men. RESULTS--The studies reviewed are all of high epidemiological quality and present a consistent and stable dose-response pattern. The aetiological fraction was estimated to be 30%, with a plausible range of 20-40%. CONCLUSIONS--Social network was an important, independent, risk factor for cardiovascular disease in white, middle aged men. It had a strong impact on mortality, comparable to that of traditional risk factors. Social network should have a more central role in future epidemiological research into cardiovascular disease. The factors that result in a strong social network should be identified and strategies applicable in preventive work should be developed.